2018
DOI: 10.3928/01913913-20180802-01
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Thickness Measurements of the Extraocular Rectus Muscle Tendons in Graves' Ophthalmopathy

Abstract: OCT emerged as an accurate method for measuring medial rectus and lateral rectus tendon thicknesses in patients with Graves' ophthalmopathy. The imaging tool was able to detect thicker horizontal rectus tendons in patients with inactive Graves' ophthalmopathy than in controls, and in patients with active compared to inactive disease. [J Pediatr Ophthalmol Strabismus. 2018;55(6):356-362.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…ОКТ переднего сегмента с расширенной глубиной визуализации (EDI AS-OCT) при ЭОП показало, что увеличение толщины сухожилий медиальной и латеральной прямых экстраокулярных мышц (ЭОМ) хорошо определяется и коррелирует с параметрами магниторезонансной томографии (МРТ) [21,41,42]. N. H ner и соавт.…”
Section: Optical Coherence Tomography and Optical Coherence Tomograph...unclassified
See 1 more Smart Citation
“…ОКТ переднего сегмента с расширенной глубиной визуализации (EDI AS-OCT) при ЭОП показало, что увеличение толщины сухожилий медиальной и латеральной прямых экстраокулярных мышц (ЭОМ) хорошо определяется и коррелирует с параметрами магниторезонансной томографии (МРТ) [21,41,42]. N. H ner и соавт.…”
Section: Optical Coherence Tomography and Optical Coherence Tomograph...unclassified
“…L. De-Pablo-G mez-de-Lia o и соавт. [42] выявили наличие корреляции между толщиной сухожилий латеральной и медиальной прямых ЭОМ (EDI AS-OCT) и CAS ЭОП. С точки зрения авторов, исследование толщины сухожилия медиальной прямой мышцы с использованием EDI AS-OCT может проводиться с целью мониторинга пациентов с ЭОП.…”
Section: Optical Coherence Tomography and Optical Coherence Tomograph...unclassified
“…Of now, a cumulative dose of 4.5-5 g of intravenous methylprednisolone is recommended for moderate-tosevere TED. 71 Kahaly et al recommended dose of IV methylprednisolone (500 mg weekly x 6 week then 250 mg weekly x 6 weeks for a total dose of 4.5g ) for TED. 72 Besides this, steroid-sparing agents like cyclosporine and MMF have also been shown to be effective in TED treatment in study conducted at Cambridge namely close endocrine control and it was observed that the early introduction of cyclosporin after initial systemic glucocorticoid immunosuppression has resulted in a 7-fold reduction in decompression surgery.…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a rapid, noninvasive, and readily available imaging modality which has become a standard of care for evaluating retina disease. Recent studies have shown that OCT is an accurate method for measuring horizontal rectus tendons, which can differentiate TED from normal eyes [8]. With the advent of swept-source OCT (SS-OCT), enhanced light penetration through the retinal pigment epithelium (RPE) enables more effective visualization of the choroidal and scleral layers [9,10].…”
Section: Introductionmentioning
confidence: 99%